Composition and distribution of non-native fishes in relation to water quality parameters in River Cauvery - K., Lohith Kumar; Gogoi, Pranab; Manna, R. K.; M., Roshith C.; S., Sibina Mol; M.E., Vijay Kumar; Suresh, V. R.; Samanta, S.; Das, B. K. (Journal of the Inland Fisheries Society of India, 2022)
Invasive non-native fishes are among the serious threats to the native fauna in freshwater ecosystems. The present study aimed to understand the diversity, distribution pattern and composition of the non-native fishes in River Cauvery. Seasonal samplings were performed at 11 stations spread over the entire stretch of the river to systematically collect the data on fish and water variables. In total, seven non-native fishes, namely, Nile tilapia Oreochromis niloticus, Mozambique tilapia O. mossambicus, African catfish Clarias gariepinus, Common carp Cyprinus carpio, Grass carp Ctenopharyngodon idella, Vermiculated sailfin catfish Pterygoplichthys disjunctivus and Three-spot cichlid Amphilophus trimaculatus were recorded, of which Three-spot cichlid was reported for the first time from the Cauvery basin. In terms of weight, non-native fishes contributed maximum (60%) to the total fish catch in the middle stretch of the river. O. niloticus was the most dominant among the non-native fishes contributing 71% to the total non-native fish catch. Cluster analysis of sampling stations based on the abundance of non- native fishes yielded two groups with 32% and 49% dissimilarity. Similarity percentage (SIMPER) routine analysis reflected that O. niloticus contributed maximum, to the tune of 87% and 77% in group I and group II, respectively. Canonical Correspondence Analysis (CCA) showed that the water variables, viz., pH, WT, TA, flow, DO and biochemical oxygen demand (BOD) mostly influenced the non-native fishes. The RESEARCH PAPER J. Inland Fish. Soc.India 2021 53 (3&4): 185-193 composition of non-native fishes showed no temporal variations, whereas, spatial differences exhibited significant heterogeneity. The study showed that invasion by non-native fishes is continuing in the river Cauvery. Result of the study will aid in devising plans for the management of the non-native fishes in the river. Further studies are needed to ascertain the ecological, economic, and social impacts of non-native fishes in the River Cauvery. Key wordsÂ Diversity; Exotics; Impact; Invasion; Management; Water quality